Analysis of 102 Fully Robotic Pancreaticoduodenectomies: Clinical and Financial Outcomes. Issue 5 (May 2020) - Mejia, Alejandro; Shah, Jimmy; Vivian, Elaina; Acharya, Priyanka
Abstract : Objectives: The value of robotic pancreaticoduodenectomy (RPD) remains undefined. The aim of this retrospective study was to compare and assess clinical outcomes and financial variables of patients undergoing RPD versus open pancreaticoduodenectomy (OPD) at a single high-volume center. Methods: The study design is a retrospective analysis of a prospectively maintained database of consecutive PD patients from 2013 to 2019. Clinical variables and total hospital charges were evaluated as an unadjusted and adjusted intention-to-treat analysis. Results: A total of 156 patients (54 OPD, 102 RPD) were identified. In the RPD group, patients were significantly older ( P = 0.0304) and had shorter length of stay (mean, 7 vs 11.8 days; P < 0.0001) and longer operative times (mean, 352.7 vs 211.5 minutes; P < 0.0001) compared with OPD. There was no significant difference in 90-day readmissions, bleeding, or complications between OPD and RPD. Adjusted charge analyses show no difference in total charges ( P = 0.057). Conclusions: Robotic pancreaticoduodenectomy is safe, feasible, and valid alternative to OPD. Because of comparable results within each group, randomized trials may be indicated. High-volume RPD centers should collaborate to better understand the differences and advantages over laparoscopic or OPD.